2019
DOI: 10.1016/j.yclnex.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some micronutrients serum levels in children with severe acute malnutrition with and without cerebral palsy- A follow up case control study

Abstract: Objective: Zinc, copper and selenium are essential for normal development and function of the central nervous system. This study aimed at assessment of serum levels of zinc, copper and selenium in children with severe acute malnutrition (SAM) with & without cerebral palsy both before and after nutritional rehabilitation. Methods: A prospective case control study involved 2 groups (Group I); included160 children with SAM of both sex, aged 6e59 months, this group was subdivided into 2equal subgroups; subgroup A:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Copper 58,59,70 All ages: 0.7-1. We recommend the use of estimating equations using both skinfold measurements and other variables, such as age and sex, developed by Oeffinger et al 31 These have shown good agreement with DXA, the functional gold standard.…”
Section: Laboratory Testing and Findingsmentioning
confidence: 99%
“…Copper 58,59,70 All ages: 0.7-1. We recommend the use of estimating equations using both skinfold measurements and other variables, such as age and sex, developed by Oeffinger et al 31 These have shown good agreement with DXA, the functional gold standard.…”
Section: Laboratory Testing and Findingsmentioning
confidence: 99%
“…Evidence has shown that managing SAM according to the WHO guidelines is effective (Bebars et al, 2019 ; Das et al, 2020 ; Desyibelew et al, 2020 ). Although the WHO guidelines are available and have been reported to be effective, some countries/hospitals in Sub‐Saharan Africa are fully, or in part, not complying with the guidelines (Mambulu‐Chikankheni et al, 2017 ; Warfa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%